(untitled) - Havel, Karel; Novak, Andrej (Doprava a spoje, 2012)
This paper describes some of the results of research project Centre of excellence for Air Transport -ITMS 26220120065, which is being elaborated at Air Transport Department of the University of Zilina and co-financed from sources of EU. The aim of the paper is to familiarize experts from other fields with issues of the flight inspection of communications, navigation and surveillance systems (CNS).